Analysis of footprints provides additional insights during monitoring of Duvaucel's geckos (Hoplodactylus duvaucelii). Issue 4 (2nd October 2017) - Harker, T. D.; Harker, N. F.; Harker, F. R.; Peace, J.; Barry, M.; Ludbrook, M. R.; Ji, W.
ABSTRACT: The use of tracking tunnels to record footprints is becoming an important tool for monitoring fauna. This study demonstrated that Duvaucel's gecko ( Hoplodactylus duvaucelii ) footprints (toe dimensions, foot length and foot area) can be used to predict snout-to-vent length (SVL). Back feet were larger than front feet and, as long as this was taken into account, all anatomical features of footprints predicted SVL with R 2 values > 0.73. Measurements of foot area were easy to make and provided R 2 values of 0.94–0.97. Footprint analysis of a population of Duvaucel's geckos on Motuora Island in the Hauraki Gulf, confirmed the presence of island-born geckos and improved estimates of the number of individuals. We propose that image analysis of footprints can be used to increase knowledge of populations of geckos that occur at low density, are cryptic and/or hard to capture, and are being monitored by volunteers.